Study Of Green Movement In Indian Corporate Houses For Sustainable Growth - Kaur, Harpinder (Gyan Management Journal, 2020)
The Green Management is the requirement of 21stcentury because of over consumption of non renewable resources as raw material by the organizations. Industrialization and urbanization has put tremendous pressure on non-renewable resources alarming the ecological and environment imbalances in the world .Green management is the organization-wide process of creating and implementing innovative techniques and initiatives to achieve long run sustainability, social responsibility, waste reduction and to build competitive advantage on the basis of green products, services .It also include integrating environmental sustainable goals and strategies withobjectives of organization .This research paper tries to explore the ways how Indian Corporate organisations of modern times are taking initiatives to become green organizations.Setting green goals and actions make a responsible ,good business sense .Data hasbeen collected for Twenty four Indian companies from journals, websites, research papers and newspapers. The paper describes the current scenario of the green movement initiatives taken by Indian corporate houses in various industries.